Commemoration of Nihat Karaman in Amsterdam. First row f.l.t.r.: Adelmund, Ter Veld, ?, Van Es. Series of 2 photos - Tuc, H.
Commemoration of Nihat Karaman in Amsterdam. First row f.l.t.r.: Adelmund, Ter Veld, ?, Van Es. Series of 2 photos.